The Akeffa Tutor Application: A New Arabic Writing System - Jamal, Amani Tariq; Aljojo, Nahla; Al-Ghamdi, Morooj Saleh; Hindi, Bashayer Abdulhakeem; Al-Ghanmi, Mashael Khaled; Al-Jahdali, Shaima Yassin; Karam, Baraa Mostafa; Abualnaja, Talah Fahad (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This paper shows an application for a new Arabic writing system, named Tala Arabic Writing System for people with visual impairments. As known, the Braille writing system is a way of communication for many people with visual impairment around the world. Among that, people who are using Arabic Braille faced many problems especially with the diacritical marks, which are written as same as the letters. That’s why a girl named Tala Abo-Alnaja invented a new Arabic writing system where letters and diacritical marks are written as geometrical shapes to make learning easier. Anyone who wants to learn and practice the Tala Arabic writing system can. Since this system is still new and an unknown system among people with visual impairments, there is lacking in learning resources. We proposed an application for teaching the Tala Arabic writing system using an external keyboard covered with plastic prominent shapes. This application was developed based on identified functional requirements and usability. The limitation of this application was center around the keyboard and the one platform it can work on (iOS), and some of the additional things like voiceOver, keyboard language, and the device sound, which added more constraints on the application. The satisfying results of the testing that gained from participants with visual impairments approved the success of this application. Akeffa Application is expected to be an effective way of learning due to the amazing feedback it had.